New Design of TV Sekolah Prototype as Innovative Learning Media for Early Childhood Education - Sri Watini (International Institute for Advanced Science & Technology (IIAST), 2025)
The COVID-19 pandemic disrupted traditional education systems, highlighting the need for digital learning solutions, especially in Early Childhood Education (ECE). This study introduces TV Sekolah, a hybrid learning platform designed to address the unique challenges of ECE by integrating synchronous virtual interaction, multimedia content, gamification, and cultural education. Existing digital platforms often lack features tailored for young children, and TV Sekolah bridges this gap with four key components: School Stage, Digital Library, Virtual Classroom, and TV Sekolah Festival, creating a comprehensive learning environment. The research uses the Successive Approximation Model (SAM) for prototype development, allowing iterative design, evaluation, and refinement with feedback from teachers, students, and stakeholders. The platform scalable technology efficiently manages video content and interactive learning, catering to diverse user needs and overcoming connectivity limitations. Preliminary feedback indicates improved learner engagement and educational outcomes. However, challenges such as limited device access and internet connectivity, especially for low income families, remain. To address these, the platform partnered with local governments to provide affordable devices and telecom companies for discounted internet packages. The education ministry also introduced training programs for teachers. This study offers solutions to these barriers and contributes to advancing hybrid learning by providing an inclusive, adaptable, and practical platform for early learners in diverse socio economic settings.